Biological Distribution of Orally Administered [123I]MIBG for Estimating Gastrointestinal Tract Absorption - Masato Kobayashi; Asuka Mizutani; Yuka Muranaka; Kodai Nishi; Hisakazu Komori; Ryuichi Nishii; Naoto Shikano; Takeo Nakanishi; Ikumi Tamai; Keiichi Kawai (MDPI AG, 2021)
Gastrointestinal tract absorption of cationic anticancer drugs and medicines was estimated using whole-body imaging following oral [123I]MIBG administration. [123I]MIBG was added to cultures of human embryonic kidney (HEK)293 cells expressing human organic anion transporting polypeptide (OATP)2B1, carnitine/organic cation transporter (OCTN)1 and OCTN2, and organic cation transporter (OCT)1, OCT2, and OCT3 with and without cimetidine (an OCTN and OCT inhibitor) and L-carnitine (an OCTN inhibitor). Biodistribution analyses and single-photon emission computed tomography (SPECT) imaging in normal and dextran sodium sulfate (DSS)-induced experimental colitis mice were conducted using [123I]MIBG with and without cimetidine. [123I]MIBG uptake was significantly higher in HEK293/OCTN1, 2, and OCT1-3 cells than in mock cells. Uptake via OCTN was inhibited by L-carnitine, whereas OCT-mediated uptake was inhibited by cimetidine. Biodistribution analyses and SPECT imaging studies showed significantly lower accumulation of [123I]MIBG in the blood, heart, liver, and bladder in DSS-induced experimental colitis mice and mice with cimetidine loading compared with normal mice, whereas significantly higher accumulation in the stomach and kidney was observed after [123I]MIBG injection. [123I]MIBG imaging after oral administration can be used to estimate gastrointestinal absorption in the small intestine via OCTN and/or OCT by measuring radioactivity in the heart, liver, and bladder.